1998
DOI: 10.1002/(sici)1096-8628(19980710)81:4<282::aid-ajmg2>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

NIMH genetics initiative millennium schizophrenia consortium: Linkage analysis of African-American pedigrees

Abstract: The NIMH Genetics Initiative is a multi-site collaborative study designed to create a national resource for genetic studies of complex neuropsychiatric disorders. Schizophrenia pedigrees have been collected at three sites: Washington University, Columbia University, and Harvard University. This article-one in a series that describes the results of a genome-wide scan with 459 short-tandem repeat (STR) markers for susceptibility loci in the NIMH Genetics Initiative schizophrenia sample-presents results for Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(89 citation statements)
references
References 47 publications
5
84
0
Order By: Relevance
“…32 Freedman et al 33 reported positive linkage of the abnormality in P50 suppression with D15S1360, a dinucleotide repeat present o120 kbp from the 5 0 end of the coding region of the alpha 7-nicotinic receptor gene (CHRNA-7), assuming an autosomal dominant mode of transmission (LOD score ¼ 5.3, Y ¼ 0.0, Po0.0001 33 ). This linkage has been replicated in several other populations including African Americans, 31 Germans, 32 Southern African Bantu families 34 and Taiwanese. 35 Several other studies have also pointed towards this region as being of significance for psychiatric disorders.…”
Section: Association Of Cyp1a2 Polymorphisms With Tardive Dyskinesiamentioning
confidence: 68%
See 1 more Smart Citation
“…32 Freedman et al 33 reported positive linkage of the abnormality in P50 suppression with D15S1360, a dinucleotide repeat present o120 kbp from the 5 0 end of the coding region of the alpha 7-nicotinic receptor gene (CHRNA-7), assuming an autosomal dominant mode of transmission (LOD score ¼ 5.3, Y ¼ 0.0, Po0.0001 33 ). This linkage has been replicated in several other populations including African Americans, 31 Germans, 32 Southern African Bantu families 34 and Taiwanese. 35 Several other studies have also pointed towards this region as being of significance for psychiatric disorders.…”
Section: Association Of Cyp1a2 Polymorphisms With Tardive Dyskinesiamentioning
confidence: 68%
“…Chromosome 15q13-15 has been found to be associated with schizophrenia in genome wide scans [30][31][32] although the criteria for linkage were fulfilled in only one study using a subtype Periodic Catatonia (15q15 at position 35.3 cM, LOD score ¼ 3.57, P ¼ 2.6 Â 10 À5 ). 32 Freedman et al 33 reported positive linkage of the abnormality in P50 suppression with D15S1360, a dinucleotide repeat present o120 kbp from the 5 0 end of the coding region of the alpha 7-nicotinic receptor gene (CHRNA-7), assuming an autosomal dominant mode of transmission (LOD score ¼ 5.3, Y ¼ 0.0, Po0.0001 33 ).…”
Section: Association Of Cyp1a2 Polymorphisms With Tardive Dyskinesiamentioning
confidence: 99%
“…14 Although CYP1A2 by itself has never been implicated in pathogenesis of schizophrenia, the neighboring loci (15q13-15) have all been implicated. [20][21][22][23] CYP1A2 (15q21) is located in the vicinity of nicotinic receptors CHRNA3, CHRNA5 and CHRNB4, localized at 15q24. CYP1A2 mRNA has been detected in the rat brain (cortex, cerebellum, brain stem, thalamus, hippocampus and striatum 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The P50 sensory gating deficit, one of the best supported endophenotypes of schizophrenia and bipolar disorder, is strongly linked to this region, 1 as are two idiopathic epilepsies. 2,3 Of the many attempts to demonstrate linkage of schizophrenia and bipolar disorder to this region, two studies showed linkage to bipolar disorder, 4,5 but several found either weak [6][7][8][9][10] or no linkage to schizophrenia. [11][12][13] Both schizophrenia and bipolar disorder have also shown association with 15q13.3 markers.…”
Section: Introductionmentioning
confidence: 99%